Equity and the Cuban National Health System's response to COVID-19 - Pedro Mas Bermejo; Lizet Sánchez Valdés; Lorenzo Somarriba López; Nelly Cristina Valdivia Onega; María Josefina Vidal Ledo; Ileana Alfonso Sánchez; Armando Seuc Jo; Yudivian Almeida Cruz; Roberto Morales Ojeda (Pan American Health Organization, 2021)
Cuba's National Health System has managed to guarantee an effective and equitable response to COVID-19. Universal and free health coverage, based on primary care, follows the principle of equity and the greatest resources are allocated to areas of the lowest socioeconomic stratum (where higher risk is concentrated), followed by those of medium and high strata, in that order. This allowed for similar mortality rates in the three strata, and Cuban national mortality rate was one of the lowest in the Region of the Americas. Before the first case was identified in Cuba, a Plan for Coronavirus Prevention and Control was elaborated with multisectoral participation, and when the first case was confirmed the Temporary National Working Group to Fight COVID-19 was created as an advisory body of the government. The actions to face the pandemic began with preventive measures in the community, continued in the isolation centers and ended again in the community with actions of surveillance and follow up of recovered patients. Following the principle of territoriality, molecular diagnosis laboratories were created in the provinces that did not have one. Free medical care and treatment; the preparation of a single national intersectoral government plan; the use of particular strategies for research, diagnosis and case tracing; and the implementation of a universal protocol for disease prevention and treatment of confirmed cases made it possible to control the disease with a health equity perspective.